1997
DOI: 10.1590/s0036-46651997000300002
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of dermatophytoses seen at University Hospital in Florianópolis, Santa Catarina, Brazil

Abstract: Dematophytoses comprise mycoses which are very frequently diagnosed in the routine of clinical laboratories of Florianópolis, like any other Brazilian cities. However, no clinical or epidemiological studies data have been published for that city so far. To partially clarify these questions, we carried out a study on this subject on patients who sought the mycology services of Hospital of Federal University of Santa Catarina, from January 1995 to November 1996. The most prevalent dermatophyte was Trichophyton r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
1
13
0
3
Order By: Relevance
“…1,[4][5][6][7][8][12][13][14][15] Fatores como condições climáticas, práticas sociais, deslocamentos cada vez mais freqüentes e hábitos de higiene certamente contribuem para as variações epidemiológicas dos dermatófitos.…”
Section: Discussionunclassified
“…1,[4][5][6][7][8][12][13][14][15] Fatores como condições climáticas, práticas sociais, deslocamentos cada vez mais freqüentes e hábitos de higiene certamente contribuem para as variações epidemiológicas dos dermatófitos.…”
Section: Discussionunclassified
“…The literature contains data collected and analyzed from the states of São Paulo 9 , Goiás 12 , Rio Grande do Sul 3 , Santa Catarina 47 , Minas Gerais 30 , Distrito Federal 8 , Amazonas 16 , Paraná 40 and Ceará 6 . However, our review found no record of any kind of study conducted in the state of Mato Grosso, despite the fact that the bioclimatic conditions are extremely favorable to the appearance of such fungal infections.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is estimated that 10-15% of the general population may be affected by these microorganisms at some time in their lives. 3,4 More than 30 species of dermatophytes have been identified; however, the great majority can be taxonomically classified into three anamorphic types: Trichophyton, Microsporum and Epidermophyton. The species most commonly reported as being the cause of infection in humans are Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis, Trichophyton tonsurans and Epidermophyton floccosum.…”
Section: Introductionmentioning
confidence: 99%
“…The geographical distribution of these species varies greatly depending on the socioeconomic, hygienic and environmental conditions of the population. [4][5][6] The risk factors associated with dermatophytoses include aging, immunosuppression, a family history of diabetes mellitus, peripheral vascular disease, skin-related disorders such as hyperhidrosis and psoriasis, the use of tight-fitting footwear and trauma to the nails. 7 Studies have shown that patients with chronic renal failure are more susceptible to dermatophytosis, principally onychomycosis, which is the second most common disorder in patients undergoing hemodialysis, with a prevalence that ranges from 6.2 to 69.8%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation